Lessons from the Crisis in Argentina - Daseking, Christina (Occasional Papers; Occasional Paper ;, 2005)
In 2001- 02, Argentina experienced one of the worst economic crises in its history. A default on government debt, which occurred against the backdrop of a prolonged recession, sent the Argentine currency and economy into a tailspin. Although the economy has since recovered from the worst, the crisis has imposed hardships on the people of Argentina, and the road back to sustained growth and stability is long. The crisis was all the more troubling in light of the fact that Argentina was widely considered a model reformer and was engaged in a succession of IMF-supported programs through much of the 1990s. This Occasional Paper examines the origins of the crisis and its evolution up to early 2002 and draws general policy lessons, both for countries' efforts to prevent crises and for the IMF's surveillance and use of its financial resources.